Early detection of pleuro‐pulmonary tuberculosis by bedside lung ultrasound: A case report and review of literature. Issue 7 (14th July 2022) - Cocco, Giulio; Boccatonda, Andrea; Rossi, Ilaria; D'Ardes, Damiano; Corvino, Antonio; Delli Pizzi, Andrea; Ucciferri, Claudio; Katia, Falasca; Jacopo, Vecchiet
Abstract: We present a case in which lung ultrasound (LUS) was relevant to reach an early diagnosis of lung tuberculosis and to manage the patient in the right setting. Moreover, ultrasound allowed to detect and treat massive pleural effusion through an ultrasound‐guided thoracentesis. Abstract : A 36‐year‐old Caucasian policeman was referred to our Emergency Department for dyspnea. He reported persistent cough and fever with night sweats for about 2 weeks, for which antibiotic therapy for 5 days without clinical benefit. Laboratory investigations revealed a C‐reactive protein of 15.10 mg/dl (n.v. 0.00–0.50). We performed a bedside lung ultrasound (LUS) that showed a massive finely corpuscular anechoic pleural effusion with thin branches of fibrin on the left, with a consolidated lung parenchyma collapsing to the hilum as for complete atelectasis; in the context of the consolidated lung parenchyma, multiple round hypo‐anechoic formations were seen, with finely irregular margins, not assuming colordoppler signal suspicious for cavitations.